APPROXIMATE SOLUTION OF NONLINEAR OIL FILM FORCES OF FINITE LENGTH SLIDE JOURNAL BEARING - HEI Di; LU ZunYou (Jixie qiangdu)
Supposing the oil film at the laminar state,an approximate analytical method is proposed for calculating nonlinear oil film forces of finite length journal bearing. The dynamic ‘π’oil film assumption is usually taken to determine nonlinear oil film forces in the dynamic analysis of hydrodynamic journal bearing-rotor system. However oil film field is not‘π’zone. In this paper,the assumption is taken that the start position of the oil film is 0,and the termination position needed to be calculated.Based on the variational principle,the separation of variables is employed to obtain the pressure distribution in this paper. The results calculated by the proposed method are in good agreement with the oil film forces by the finite element method. Meanwhile,the influence of the parameters on the oil film forces is analyzed.